A review on the anthocyanin and antioxidant capacities of Clitoria ternatea flower / Khalimatul Saadiah Jamsari, Eddie Ti Tjih Tan and Siti Azima Abdul Muttalib - Jamsari, Khalimatul Saadiah; Eddie, Ti Tjih Tan; Abdul Muttalib, Siti Azima (2021)
Butterfly pea flower has been used as food colourant for decades by Malaysians, purposely to add an aesthetical value to the food. Besides, the flower has been scientifically displaying several bioactivities properties. A multitude of works on the antioxidant capacity of butterfly pea has been presented in literature and the antioxidant capacities are correlated with the presence of polyphenolic compounds. Hence, this review aims to understand the correlation between anthocyanin, phenolic compounds and antioxidant activity of butterfly pea flowers. The finding from this review unveils that antioxidant capacity of butterfly pea are depending on the number of hydroxyl groups attached on the carbon 3' and 4' of ring B, the availability of main reactive sites for nucleophilic and electrophilic attacks, as well as the presence of electron donor on the chemical structure of the bioactive compounds. Furthermore, high antioxidants are obtained in the solvent extraction that has been added with acid. The protonation-deprotonation process of the anthocyanin at various pH is the main factor that contributed to the antioxidant activity. Thus, a comprehensive study on the antioxidant properties of butterfly pea flower as a natural antioxidant towards foods is recommended to widen the application of butterfly pea in the food industry.